2020
DOI: 10.3389/fmed.2020.00264
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tumor Budding With Immune Evasion Pathways in Primary Colorectal Cancer and Patient-Derived Xenografts

Abstract: Tumor budding has been found to be of prognostic significance for several cancers, including colorectal cancer (CRC). Additionally, the molecular classification of CRC has led to the identification of different immune microenvironments linked to distinct prognosis and therapeutic response. However, the association between tumor budding and the different molecular subtypes of CRC and distinct immune profiles have not been fully elucidated. This study focused, firstly, on the validation of derived xenograft mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Tumor budding in CRC is defined as a single tumor cell or a cell cluster of up to four tumor cells, assessed in one hotspot (in a field measuring 0.785 mm 2 ) at the invasive front [ 12 , 13 ]. Studies have indicated a close link between tumor budding and a distinctive immune-suppressing microenvironment that promotes tumor invasion in gastric adenocarcinoma [ 14 ], stage I lung adenocarcinoma [ 15 ], pancreatic cancer [ 16 ], and CRC [ 17 ]. Nevertheless, the crosstalk between fibroblasts and tumor buds, and the mechanism through which the crosstalk occurs remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor budding in CRC is defined as a single tumor cell or a cell cluster of up to four tumor cells, assessed in one hotspot (in a field measuring 0.785 mm 2 ) at the invasive front [ 12 , 13 ]. Studies have indicated a close link between tumor budding and a distinctive immune-suppressing microenvironment that promotes tumor invasion in gastric adenocarcinoma [ 14 ], stage I lung adenocarcinoma [ 15 ], pancreatic cancer [ 16 ], and CRC [ 17 ]. Nevertheless, the crosstalk between fibroblasts and tumor buds, and the mechanism through which the crosstalk occurs remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is supported by a recent study by Sadozai et al, which demonstrated that extensive tumor budding is accompanied by diminished anti-tumor immunity and higher B7-H3 (CD276) expression [ 33 ]. In colorectal cancer, high-grade tumor budding is associated with an up-regulation of negative regulatory immune checkpoints and immune evasion [ 34 ]. We and others identified tumor budding as the independent prognostic factor in pancreatic cancer [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In region IM-A, tumor cells having poorly differentiated morphology invade the underlying stroma and classical budding is observed. This is a consequence of reduced cell-cell cohesion and is associated with metastasis and poor prognosis (Guil-Luna et al, 2020). Tumor buds are classically defined ≤4 cells in a cluster surrounded by stroma (Lugli et al, 2017a), but 3D reconstruction shows that these represent the termini of extended fibrillary structures whose distal tips generate the bud morphology in cross-section (Bronsert et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this case, however, PD-L1 + macrophages were the immune cells most frequently in contact with CD8 + PD1 + T cells; in contrast, PD-L1 expression on tumor cells was low and few Tregs were present. Thus, the established connection between tumor budding, metastasis and disease recurrence is likely to reflect the presence of tumor cells undergoing EMT (and developing the ability to disseminate) as well as a permissive and immunosuppressive environment(Guil-Luna et al, 2020).…”
mentioning
confidence: 99%